Understanding the Effect of Introducing Micro- and Nanoparticle Bismuth Oxide (Bi2O3) on the Gamma Ray Shielding Performance of Novel Concrete - Mohamed A. El-Nahal (MDPI AG, 2021)
The aim of this study is to investigate the radiation shielding properties of novel concrete samples with bulk Bi2O3 and Bi2O3 nanoparticles (Bi2O3 NP) incorporated into its composition. The mass attenuation coefficient of the concrete samples without Bi2O3 and with 5 and 7 wt% bulk Bi2O3 were experimentally determined and were compared against values obtained using the XCOM and Geant4 simulations. Both methods greatly agree with the experimental values. The linear attenuation coefficients (LAC) of blank concrete (C-0), concrete with 5% bulk Bi2O3 (C-B5), and concrete with 5% nanoparticle Bi2O3 (C-N5) were determined and compared at a wide energy range. We found that the LAC follows the trend of C-0 < C-B5 < C-N5 at all the tested energies. Since both C-B5 and C-N5 have a greater LAC than C-0, these results indicate that the addition of Bi2O3 improves the shielding ability of the concretes. In addition, we investigated the influence of nanoparticle Bi2O3 on the LAC of the concretes. The half-value layer (HVL) for the concretes with bulk Bi2O3 and Bi2O3 nanoparticles is also investigated. At all energies, the C-0 has the greatest HVL, while C-N15 has the least. Thus, C-N15 concrete is the most space efficient, while C-0 is the least space efficient. The radiation protection efficiency (RPE) of the prepared concretes was found to decrease with increasing energy for all five samples. For C-0, the RPE decreased from 63.3% at 0.060 MeV to 13.48% at 1.408 MeV, while for C-N15, the RPE decreased from 87.9 to 15.09% for the same respective energies. Additionally, C-N5 had a greater RPE than C-B5, this result demonstrates that Bi2O3 NP are more efficient at shielding radiation than bulk Bi2O3.